PENGARUH KEDISIPLINAN GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SMP NEGERI 1 JEREWEH - Prihatin, Umul Hani; Rahmawati, Fitri; Afian, Tilal (Universitas Pendidikan Mandalika, 2023)
Abstract: This research aims to determine the influence of teacher discipline on students' learning motivation at SMPN 1 Jereweh. The type of research used in this research is quantitative descriptive. This research was carried out from April to May 2023 in class VIII at SMP Negeri 1 Jereweh, West Sumbawa Regency, for the 2022/2023 academic year. The population in this study were all class VIII students. The sample used in this research was class VIII D. The data collection technique was administering teacher discipline and student motivation questionnaires, interviews with school principals and subject teachers, and documentation. The data analysis technique was carried out using four grading scales for answers: very good was given a score of 4, good was given a score of 3, less good was given a score of 2, and not good was given a score of 1. The results of the research found that teacher discipline was influenced in learning activities in the excellent category, with a score of 50.1%. Students learning motivation is in a suitable category. The discipline of teachers at SMPN 1 Jereweh in student learning activities is suitable. Students' learning motivation, which is influenced by internal and external factors, is in the excellent category.Keywords: Teacher Discipline, Learning MotivationAbstrak: Penelitian ini bertujuan untuk mengetahui pengaruh kedisiplinan guru terhadap motivasi belajar peserta didik di SMPN 1 Jereweh. Jenis penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. Penelitian ini dilaksanakan dari Bulan April sampai Bulan Mei 2023 pada kelas VIII di SMP Negeri 1 Jereweh Kabupaten Sumbawa Barat Tahun Pelajaran 2022/2023. Populasi dalam penelitian ini adalah seluruh siswa kelas VIII. Sampel yang di gunakan dalam penelitan ini adalah kelas VIII D. Teknik pengumpulan data yang digunakan melalui pemberian angket kedisiplinan guru dan motivasi peserta didik, wawancara dengan kepala sekolah dan guru mata pelajaran, dan dokumentasi. Teknik analisis data dilakukan dengan menggunakan 4 skala pemberian nilai dilakukan untuk jawaban sangat baik diberi nilai 4, baik diberi nilai 3, kurang baik diberi nilai 2, dan tidak baik diberi nilai 1. Hasil penelitian ditemukan adanya pengaruh kedisiplinan guru dalam kegiatan pembelajaran kategori baik dengan skor 50,1%. Motivasi belajar peserta didik masuk kategori baik. Dapat disimpulkan kedisiplinan guru di SMPN 1 Jereweh dalam kegiatan pembelajaran terhadap peserta didik masuk kategori baik. Motivasi belajar peserta didik yang dipengaruhi faktor internal dan eksternal masuk kategori baik.Kata Kunci: Kedisipilinan Guru, Motivasi Belajar